Molecular Architecture of Genetically-Tractable GABA Synapses in C. elegans - Zhou, Xin; Bessereau, Jean-Louis (Frontiers in Molecular Neuroscience, 2019)
Inhibitory synapses represent a minority of the total chemical synapses in the mammalian brain, yet proper tuning of inhibition is fundamental to shape neuronal network properties. The neurotransmitter γ-aminobutyric acid (GABA) mediates rapid synaptic inhibition by the activation of the type A GABA receptor (GABAAR), a pentameric chloride channel that governs major inhibitory neuronal transduction in the nervous system. Impaired GABA transmission leads to a variety of neuropsychiatric diseases, including schizophrenia, autism, epilepsy or anxiety. From an evolutionary perspective, GABAAR show remarkable conservations, and are found in all eukaryotic clades and even in bacteria and archaea. Specifically, bona fide GABAARs are found in the nematode Caenorhabditis elegans. Because of the anatomical simplicity of the nervous system and its amenability to genetic manipulations, C. elegans provide a powerful system to investigate the molecular and cellular biology of GABA synapses. In this review, we will introduce the structure of the C. elegans GABAergic system and describe recent advances that have identified novel proteins controlling the localization of GABAARs at synapses. In particular, Ce-Punctin/MADD-4 is an evolutionarily-conserved extracellular matrix protein that behaves as an anterograde synaptic organizer to instruct the excitatory or inhibitory identity of postsynaptic domains.